The impact of ethical feedback on moral emotions and managerial behavior: A labor market experiment - Alexia Gaudeul; Katharina Gangl; Oliver Kirchkamp; Louisa Kulke (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2024)
We investigate the influence of ethical feedback on decision-makers' behavior, focusing on the role of emotions in mediating this relationship. We examine how emotions generated by ethical feedback impact subsequent decisions in a laboratory setting with incentivized tasks. We distinguish between the direct informational impact of feedback and its indirect impact mediated by emotions. This research is pioneering in linking emotions to ethical decisions in a controlled environment. The findings reveal that ethical feedback positively affects ethical behavior in an artificial labor market, whereby decision-makers set higher wages when they expect to receive ethical feedback. Surprisingly however, public feedback has a less positive effect than private feedback. We confirm that emotions mediate some of the impact of feedback on wages. We find that deciders adjust wages downward when good feedback generated positive emotions, while we expected that they would aim for maintenance of such positive emotions by maintaining wages. We discuss the need for robustness tests for theories of emotions as drivers of behavior and underscore the importance of examining deciders' intentions and their interpretations of public and private feedback.
Keywords: C92; D91; D23; 330; emotions; Ethical feedback; incentives